Association of Lung Capacity with Playing Instruments and Singing - Daquila, Cydney E. (My University, 2020)
Many hospitals have introduced music therapy programs for their patients with respiratory issues. But the question is raised, is it effective? Our research is looking at the association of lung capacity’s with musicians playing woodwind or brass instruments and singing versus those who do not. We are trying to see if having played these instruments over time or having vigorously sung over time affects a person’s Forced Vital Capacity, which is a measure of how well a person’s lungs forcibly exhale. We are also looking to see if it affects their Tidal Volume, a baseline measurement of the amount of air that can be inhaled or exhaled during one regular respiratory cycle. We are looking at these values to see if there are any associations found within these groups. We hope this research will provide a better understanding on how or if music therapy can achieve its goal in improving lung function.